Hábitos nocivos en el adulto mayor con multimorbilidad - Santos Luna, Jovanny Angelina; Iraizoz Barrios, Ana María; García Mir, Viviana; Brito Sosa, Germán; Jaramillo Simbaña, Raquel Magali; León García, Gisela de los Ángeles; Solorzano Solorzano, Stalin Lorenzo; Fajardo Aguilar, Graciela Maribel (My University, 2022)
The prevalence of multimorbidity, the simultaneous presence in an individual of two or more chronic diseases or disa-bilities, increases with age, which makes it necessary to correct the habits and lifestyles of the geriatric population to achieve an active and satisfactory old age. The objective of the work was to determine the presence of harmful health habits in older adults with multimorbidity in the province of El Oro, Ecuador. A descriptive, observational and cross-sectional study was carried out in adults over 65 years of age, between September 2019 and November 2020. The sample was 398, selecting 181 older adults who presented multimorbidity. The following questionnaires were used: “Biopsychosocial assessment of the elderly from a bioethical approach”, and the WHOQOL-BREF, evaluating harmful habits and lifestyles. Univariate, bivariate and multivariate descriptive statistics were used. The average number of illnesses was 2.9 ± 1.2 with a range between 2 and 8 illnesses. 22.1% presented more than four illnesses / disabilities. Arterial hypertension prevailed. Most of the older adults with multimorbidity did not refer to the consumption of foods that were harmful to health or toxic habits, however, they did not have enough sports and recreational or leisure activities. Women with multimorbidity had a more active life, carried out more recreational, social and exercise activities, and reported a greater capacity to carry out activities of daily life, and greater enjoyment of life than men.
La prevalencia de multimorbilidad, presencia simultánea en un individuo de dos o más enfermedades crónicas o disca-pacidades, aumenta con la edad, lo que hace necesario corregir los hábitos y estilos de vida de la población geriátrica para lograr una vejez activa y satisfactoria. El objetivo del trabajo fue determinar la presencia de hábitos nocivos a la salud en adultos mayores con multimorbilidad de la provincia de El Oro, Ecuador. Se realizó unestudio descriptivo, observacional y transversal, en adultos mayores de 65 años, entre septiembre del 2019 y noviembre del 2020. La muestra fue de 398, seleccionando 181 adultos mayores que pre-sentaban multimorbilidad. Se utilizaron los cuestionarios: “Valoración biopsicosocial del adulto mayor desde un enfoque bioético”, y el WHOQOL-BREF, evaluándose los hábitos y estilos de vida perjudiciales. Se empleó estadística descriptiva univariada, bivariada y multivariada.El promedio de enfermedades fue de 2,9±1,2 con un rango entre 2 y 8 enfermedades. El 22,1% presentó más de cuatro enfermedades/incapacidades. Prevaleció la hipertensión arterial. La mayoría de los adultos mayores con multimorbilidad no refirieron consumo de alimentos nocivos a la salud, ni hábitos tóxicos, sin embargo, sí presentaron poca práctica deportiva y actividades recrea-tivas o de ocio. Las mujeres con multimorbilidad presentaron una vida más activa, realizaban más actividades recreativas, sociales, ejercicios, y refirieron una mayor capacidad de realizar las actividades de la vida diaria, y un mayor disfrute de la vida que los hombres. Palabras Clave: Adulto mayor; multimorbilidad; nutrición del anciano; aptitud física; actividad física; recreación; estilo de vida; calidad de vida.
Keywords: ADULTO MAYOR; MULTIMORBILIDAD; NUTRICIÓN DEL ANCIANO; APTITUD FISICA